2014
DOI: 10.1002/pat.3245
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature and fiber structure on the dielectric properties of polypropylene fibrous structures

Abstract: In this work, dielectric spectroscopy was conducted on five commercial woven polypropylene‐based fabrics. Measurements of dielectric loss tangent, the effective relative dielectric permeability and ac electrical conductivity were performed over a wide range of temperature and frequency. The results in temperature range from 250 K to 355 K showed that the samples with lower value of volume fraction whose yarn is made from a short fiber have a lower value of the above mentioned dielectric parameters than the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…Izci and Bowler measured ε ′ in the frequency range of 10 −2 to 10 6 Hz and reported that ε ′ decreased only slightly, by about 0.5%. Also, in the our previous paper, we did not observe significant changes of ε ' with the frequency increase for fibrous iPP samples …”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…Izci and Bowler measured ε ′ in the frequency range of 10 −2 to 10 6 Hz and reported that ε ′ decreased only slightly, by about 0.5%. Also, in the our previous paper, we did not observe significant changes of ε ' with the frequency increase for fibrous iPP samples …”
Section: Resultsmentioning
confidence: 50%
“…Also, in the our previous paper, we did not observe significant changes of ε' with the frequency increase for fibrous iPP samples. 21 The plot of a relative dielectric constant versus frequency of the pure aPS sheet and 9 composites based on the aPS is shown in Figure 6. It can be observed that the results for the composites based on aPS, for the frequency dependence of ε′, were similar as for the With this kind of treatment, most of the alkali metal particles were implemented into the polymer matrices of iPP and aPS, which is shown by ICP-OES.…”
Section: Dielectric Spectroscopymentioning
confidence: 99%
“…A detailed description of the measurement set up is given in Refs. 18,19,31. The samples were sandwiched between two electrodes with a diameter of 13 mm.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…[18][19][20][21][28][29][30][31][32][33][34][35][36][37][38] The comparison between dielectric permittivity of the samples made from PET, PA 6.6 monofilaments, and a sample PA 6.6 monofilament with CF was performed in the frequency range from 20 Hz to 3 MHz at room conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation